Building Energy System Design and Planning: The Universidad de Santander Case - I.D. Serna Suárez; A. Martínez Gonzalez; S. Urbano Contreras (Journal of Sustainability Perspectives, 2021)
Renewable generation is gaining more thrust as the time passes, however, the growth rate of such production has been faster than the rate of the electrical grid modernization. This growth comes with great opportunities and challenges for building energy system (BES) design and planning. In this respect, this paper presents the experience and lessons learned from the design and planning of the BES of the “Universidad de Santander” (UDES) central campus. This BES renewable generation is composed of a rooftop PV system distributed across the campus buildings. The system started with 30 kWp of installed capacity (100 kWh/day on average) and now is ready to deliver near 300 kWh/day thanks to 70 kWp of extra capacity installed. In general, the implementation has been a success that now is being replied in other UDES’ campuses, and the decision taking involved highlighted the importance of a proper energy efficiency policy and electrical regulation analysis.